A longitudinal study of student and experienced nurses' self-concept. - Cowin, L; Craven, R; Johnson, M; Marsh, H (2006)
Researchers continue to emphasise the importance of professional identity or nurses' self-concept in the retention debate, although limited research has been undertaken on this specific issue. The purpose of this study was to capitalise upon recent advances in self-concept theory and measurement to identify, compare, and contrast the development of self-concept for graduate and experienced nurses. The Self Description Questionnaire III was used to assess four areas of general self-concept and a newly developed Nurses Self-Concept Questionnaire was used to assess six domains of self-concept specific to nursing. Student nurses completed instrumentation during their final year of a University course (N=506) and 6 months after graduation (N=110). Experienced nurses completed instrumentation at the end of the year (N=528) and eight months later (N=332). The results revealed that graduate self-concept was lower than experienced nurse self-concept in most domains at initial measurement (Time 1). Whilst some graduate self-concept domains demonstrated a rise in mean scores at eight months (Time 2), scores remained significantly lower overall than those of experienced nurses. The domain of Nurse General Self-Concept had fallen significantly from the student to graduate experience. Little change in the self-concept domains occurred over time for the experienced nurse group. The results provide valuable empirical evidence elucidating the development of nurses' self-concept. Key implications include the need to monitor self-concept development in graduate nurses and develop strategies for self-concept enhancement particularly for new graduates' Nurse General Self-Concept.